Clustering Runners’ Response to Different Midsole Stack Heights: A Field Study - Kögel, Jannik; Huerta, Stacy; Gambietz, Markus; Ullrich, Martin; Heyde, Christian; Dorschky, Eva; Eskofier, Björn (Sensors, 2024)
Advanced footwear technology featuring stack heights higher than 30 mm has been proven to improve running economy in elite and recreational runners. While it is understood that the physiological benefit is highly individual, the individual biomechanical response to different stack heights remains unclear. Thirty-one runners performed running trials with three different shoe conditions of 25 mm, 35 mm, and 45 mm stack height on an outdoor running course wearing a STRYD sensor. The STRYD running variables for each participant were normalized to the 25 mm shoe condition and used to cluster participants into three distinct groups. Each cluster showed unique running patterns, with leg spring stiffness and vertical oscillation contributing most to the variance. No significant differences were found between clusters in terms of body height, body weight, leg length, and running speed. This study indicates that runners change running patterns individually when running with footwear featuring different stack heights. Clustering these patterns can help understand subgroups of runners and potentially support running shoe recommendations.
CRIS-Team Scopus Importer:2024-11-08
Keywords: cluster analysis; principal component analysis; running biomechanics; running shoes; wearable sensor